A79 CHARACTERISTICS OF PEDIATRIC INFLAMMATORY BOWEL DISEASE AT DIAGNOSIS RELATED TO EARLIER USE OF BIOLOGIC THERAPY. (15th March 2019) - Mulder, D J; Zachos, M; Issenman, R; Sherlock, M
Abstract: Background: Inflammatory bowel disease (IBD) is usually treated with increasingly potent anti-inflammatory and immunomodulator medications. One of the most efficacious medication classes currently available are biologic agents. Initiation of biologic therapy is often delayed until other therapies are tried. Often, features suggestive of severe disease course are used as justification for starting biologics. However, it is unclear if disease severity is truly connected to biologic response. Aims: Clinical, biochemical, and radiographic characteristics can identify pediatric patients with IBD at diagnosis who receive biologic therapy earlier than those without these characteristics. Methods: Charts of all pediatric patients with IBD followed at our centre were reviewed. Kaplan-Meier curves were evaluated comparing characteristics at diagnosis with time to initiation of biologics. Results: Data from 198 patients followed at our centre between 2001 and 2015 was analyzed, 57.6% of patients had Crohn's disease (CD), 27.8% had ulcerative colitis (UC), and 14.6% had IBD-unclassified. The mean follow up time was 47.8 months, and ranged from 9 to 181 months. Overall, 55.5% of the patients received biologics, the mean time to biologic initiation was 21.5 months. Characteristics at diagnosis that were associated with earlier initiation of biologics based on Kaplan-Meier curves for both CD and UC were: older age, higher disease activity index and lower serum albumin level. Conclusions: In our cohort, older patients with more severely active disease and lower serum albumin levels at the time of IBD diagnosis were more likely to initiate biologic therapy earlier than those without these characteristics. Identification of these characteristics may help inform decisions to initiate biologics earlier in the IBD disease course. Prospective studies are needed to better understand how to identify patients with IBD who would benefit from starting biologic therapy at diagnosis. Funding Agencies: None